KEBEBASAN BERPENDAPAT MELALUI FACEBOOK DAN TWITTER: STUDI KASUS UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Pratiwi, Tika Ardillaning; Bungin, Burhan; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2015)
Freedom of speech is a right of every individual to the community to express their opinions either incriticism, suggestion/comment, or opinion through various ways whether oral or in writing, directly orindirectly by utilizing social media, such as facebook, twitter, etc. However, sometimes peoples out ofcontrol using their freedom of rights, so there are others who feel offended and aggrieved. Such eventsare already common, and should end up in prison. Based from this incident, researchers wanted to knowwhether freedom of speech through facebook and twitter being limited to the existence of the law ofinformation and electronic transaction (UU ITE). This research uses narrative qualitative researchdesign, which this research aimed to describe and analyze phenomena, events, social activities, attitudes,perceptions, and thought of someone about freedom of speech through facebook and twitter being limitedby the existence of the law of the information and electronic transactions (UU ITE) are presented innarrative form. From the results of this research revealed that a person’s freedom of speech throughsocial media (facebook and twitter) is not to be limit, thus they feel comfortable because of their privacyrights are protected. In this law provides legal protection to every user virtual world of criminals whoexploit information technology, computer, and internet networks.Keywords: freedom of speech, social media, facebook, twitter, UU ITE